A multidimensional strategy for uncovering comprehensive quality markers of Scutellariae Radix based on UPLC-Q-TOF-MS analysis, artificial neural network, network pharmacology analysis, and molecular simulation - Liu, Meiqi; Zhao, Xiaoran; Wen, Jinli; Sun, Lili; Huang, Rui; Zhang, Huijie; Liu, Yi; Ren, Xiaoliang (Frontiers in Plant Science, 2024)
Scutellariae Radix (SR), derived from the root of Scutellaria baicalensis Georgi, is a traditional Chinese medicine (TCM) for clearing heat and cooling blood. It has been used as a traditional herbal medicine and is popular as a functional food in Asian countries today. However, the quality of SR is influenced by various factors, and the existing standards do not fully reflect its quality. Therefore, there is an urgent need to establish a comprehensive method to evaluate its quality and discover quality markers.Firstly, UPLC-Q-TOF-MS technology was used to identify 35 chemical components qualitatively. Then, a star point design-response surface method was employed to determine the optimal ultrasound extraction process for SR. Furthermore, fingerprinting and artificial neural networks were used to grade and evaluate the quality. The results showed that the primary factors affecting the quality of SR were its growth years. The geographic origin of SR was identified as a secondary factor affecting its quality. Processing also had a significant impact on its quality, with carbon-fried products showing the most significant variation in chemical component content. Finally, through the integration of network pharmacology and molecular simulation techniques, it was determined that baicalin, baicalein, wogonin, norwogonin, norwogonin-8-O-glucuronide, skullcapflavone II, hispidulin, 8, 8"-bibaicalein, and oroxylin A-7-O-beta-D-glucuronide could serve as quality markers for SR.